The Influence of Brand Image, Service and Product Quality on Customer Loyalty of Make-Up Artist Services in Yogyakarta - Rohayati, Risma; Gunawan, Hamzah (Research Horizon, 2024)
Customer loyalty towards Make-Up Artist (MUA) services in the Special Region of Yogyakarta is the focus of this study, which seeks to investigate the effect of brand image, service quality, and product quality. The researchers in this study used a quantitative approach. All clients in the Special Region of Yogyakarta who have used the services of a Make-Up Artist (MUA) will be the focus of this research. In 2024, the research will take place between May and June. Primary and secondary data are both used in this study. The population's size is a mystery, and it's endless. We used the Lemeshow technique to choose 100 respondents for our research, which allowed us to achieve a 95% confidence level and a 5% margin of error. The quota sampling method is used in the data collecting strategy. In this study, we use brand image (X1), service quality (X2), and product quality (X3) as independent factors. The loyalty of customers is the dependent variable (Y). The study employs an operational definition that encompasses indicators and variables, with the measuring scale using a Likert scale. The instrument was subjected to validity and reliability assessment by the research team. A battery of standard hypothesis tests, including those for normality, multicollinearity, heteroscedasticity, and descriptive statistics, were used in the study. The SPSS statistics 27 was used in the data analysis procedure. Research conducted in the Special Region of Yogyakarta found that customer loyalty is positively and significantly impacted by the brand image, service quality, and product quality of Make-Up Artist (MUA) services.